The Challenges Affecting the Provision of Healthcare Services to People With Disabilities in Mukuju Sub-county, Tororo District - Elizabeth Anyango (Uganda Christian University, 2025)
This research report was undertaken to investigate the challenges affecting the provision of healthcare services to people with disabilities in Mukuju Sub-County, Tororo District. It was guided by three objectives; to assess the accessibility of healthcare facilities for people with disabilities in Mukuju Sub-County, to evaluate the capacity of healthcare workers in providing disability-inclusive services in Mukuju Sub-County, to identify the socio-economic and infrastructural barriers to healthcare access for people with disabilities in Mukuju Sub-County. The researcher used a sample size of 63 respondents then used questionnaires and interview guide to collect data which was later analyzed using the statistical package for social sciences. Results of the first objective shows that accessibility of healthcare facilities has a significant effect on people with disabilities in Mukuju Sub-County, Supported by the following responses; 62% were positive to the statement that high medical costs and lack of affordable healthcare services prevent people with disabilities from receiving necessary treatment; 61% of the respondents were positive to the statement that stigma and discrimination from healthcare providers discourage people with disabilities from seeking medical attention. Results of the second objective showed that capacity of healthcare workers has a significant effect on disability-inclusive services in Mukuju Sub-County and was supported by the following responses which include; 80% of the respondents were positive to the statement that lack of sign language skills among healthcare providers creates communication barriers for patients with hearing impairments, it can be observed that 57% were positive to the statement that shortage of healthcare workers trained in rehabilitation services limits support for individuals with physical disabilities, 51% were positive to the statement that heavy workloads and understaffing reduce the time healthcare workers can dedicate to providing disability-inclusive services while results of the third objective indicated that socio-economic and infrastructural barriers have a significant effect on healthcare access for people with disabilities in Mukuju Sub-County. There is need for the government to prioritize and invest in the integration of disability-inclusive practices in all healthcare systems to ensure equitable access for people with disabilities. This begins with formulating and enforcing policies that mandate disability-friendly standards in all public and private health facilities. The government should increase budget allocations to support construction and renovation of hospitals and clinics to meet universal design standards.